2013
DOI: 10.1016/j.media.2013.02.003
|View full text |Cite
|
Sign up to set email alerts
|

Segmentation of the luminal border in intravascular ultrasound B-mode images using a probabilistic approach

Abstract: Intravascular ultrasound (IVUS) is a catheter-based medical imaging technique that produces cross-sectional images of blood vessels and is particularly useful for studying atherosclerosis. In this paper, we present a computational method for the delineation of the luminal border in IVUS B-mode images. The method is based in the minimization of a probabilistic cost function (that deforms a parametric curve) which defines a probability field that is regularized with respect to the given likelihoods of the pixels… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
36
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(36 citation statements)
references
References 38 publications
(40 reference statements)
0
36
0
Order By: Relevance
“…This method is capable of depicting the discrepancy (agreement) between two 2D/3D outlines and has been used recently by a number of investigations. [38][39][40][41][42] Although the Bland-Altman plot 43 is widely used to analyze the agreement between two measures, it is not suitable for this study. The Bland-Altman is designed to visualize the relationship between two one-dimensional measures (assays), where the mean of the two measurements is used as the abscissa (xaxis) value, and the difference between the same two measurements is used as the ordinate (y-axis) value.…”
Section: Discussionmentioning
confidence: 99%
“…This method is capable of depicting the discrepancy (agreement) between two 2D/3D outlines and has been used recently by a number of investigations. [38][39][40][41][42] Although the Bland-Altman plot 43 is widely used to analyze the agreement between two measures, it is not suitable for this study. The Bland-Altman is designed to visualize the relationship between two one-dimensional measures (assays), where the mean of the two measurements is used as the abscissa (xaxis) value, and the difference between the same two measurements is used as the ordinate (y-axis) value.…”
Section: Discussionmentioning
confidence: 99%
“…To date, many methods have been developed for the segmentation of various ultrasound images, including breast ultrasound images, 3,4 liver tumor ultrasound images, 5 echocardiography, 6,7 prostate ultrasound images, 8,9 intravascular ultrasound images, [10][11][12][13] and some ultrasound images of other organs or tissues. 14 As Huang et al 15 indicated, the active contour model (ACM) was widely used in the segmentation of all types of ultrasound tumor images in past decades.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the compute-aided segmentation is also used in our diagnostic tool. It applied the image processing technology to analyze the medical image and facilitates the location of the lesion, which has been successfully applied in many medical fields, such as detection of atherosclerotic plaque [3], retinal hemorrhage [4] and femoral head necrosis [5].And whether the manual diagnosis or the compute-aided segmentation relies on the acoustic characteristics because it facilitates the discrimination between different tissues and lesions in vivo.…”
Section: Introductionmentioning
confidence: 99%